2010
DOI: 10.1590/s1679-62252010000400009
|View full text |Cite
|
Sign up to set email alerts
|

Morphological development of Anchoviella vaillanti (Steindachner, 1908) (Clupeiformes: Engraulidae) larvae and early juveniles

Abstract: The considerable similarity in the early life stages of different fish species makes egg and larvae identification in fishery biology and ichthyoplankton surveys a difficult task. Knowledge on early larval development of morphologically similar taxa and species-rich orders, such as Clupeiformes, mainly in the Neotropical fresh waters is rather limited. The aim of the present study was to describe morphological and meristic aspects of the larvae and early juveniles of Anchoviella vaillanti, an endemic species o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
2
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
3
2
0
1
Order By: Relevance
“…There were two oil globules observed at this stage, while Kulkarni (1950) observed three oil globules for newly 2 2 2 2 hatched larvae. In this study, there was no pigmentation in eye and mouth was close at the yolk sac larvae and the same observation was found with larvae (Silva 2010).…”
Section: Mouth Morphological Development Of T Ilisha Larvaesupporting
confidence: 87%
“…There were two oil globules observed at this stage, while Kulkarni (1950) observed three oil globules for newly 2 2 2 2 hatched larvae. In this study, there was no pigmentation in eye and mouth was close at the yolk sac larvae and the same observation was found with larvae (Silva 2010).…”
Section: Mouth Morphological Development Of T Ilisha Larvaesupporting
confidence: 87%
“…An open and active mouth was observed at this stage. Silva et al (2010) observed same characteristics for Anchoviella vaillanti. He, however, observed myomeres from 31 to 45 while this study observed 42 to 44 myomeres.…”
Section: Juvenile Stagesupporting
confidence: 64%
“…In laboratory, fish larvae were sorted out from other zooplanktonic organisms using a dissecting microscope. Larvae and juveniles of T. ilisha were differentiated from other zooplanktons collected based on common distinguishing characteristics of clupeiformes, such as; high number of myomeres, vertebrae and different fin position compare with other fish families (Silva et al, 2010;Leis and Carson-Ewart, 2000;Leis and Trnski, 1989).…”
Section: Methodsmentioning
confidence: 99%
“…Por outro lado, estudos que descrevem o desenvolvimento embrionário e larval a partir de reprodução induzida (Borçato et al 2004, Pereira et al 2006 ou do meio natural (França et al 2007, Silva et al 2010, trazem contribuições importantes para os pesquisadores que precisam ou preferem diferenciar com exatidão os 'morfotipos' encontrados em suas amostras, sem recorrer às análises de DNA. A identificação mediada por caracteres morfológicos é difícil de executar na região neotropical, uma vez que as chaves de identificação disponíveis estão aquém da elevada diversidade ictiofaunística conhecida (Reis et al 2003), mas constitui uma técnica robusta, através da qual, é possível reconhecer os caracteres merísticos e morfométricos dos peixes, que experimentam Oecol.…”
Section: Discussionunclassified